2017
DOI: 10.1007/s00268-017-4359-y
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Preoperative Hematocrit and Transfusion with Mortality in Patients Undergoing Elective Non‐cardiac Surgery

Abstract: Healthcare providers making preoperative clinical decisions for patients undergoing elective surgery should consider the degree of preoperative anemia and likelihood of perioperative transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…Stratification of the matched cohort by preoperative hematocrit revealed significantly increased risk of bleeding with decreasing levels of hematocrit (Table ). These findings are congruent with those published by Gabriel et al, a study that examined preoperative hematocrit in noncardiac surgery …”
Section: Discussionsupporting
confidence: 93%
“…Stratification of the matched cohort by preoperative hematocrit revealed significantly increased risk of bleeding with decreasing levels of hematocrit (Table ). These findings are congruent with those published by Gabriel et al, a study that examined preoperative hematocrit in noncardiac surgery …”
Section: Discussionsupporting
confidence: 93%
“…Prior literature has shown similar associations between pre- and postoperative transfusion and morbidity and mortality [ 8 ]. In the preoperative setting, Gabriel et al used a sample of noncardiac surgical cases from NSQIP to show an independent association between preoperative and perioperative transfusion with mortality.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies have compared liberal (hemoglobin < 10 g/dL) and restrictive (hemoglobin < 8 g/dL or symptomatic) transfusion guidelines in an attempt to discern at which point the harm of transfusion outweighs the benefits. Carson et al demonstrated no difference in mortality, inability to walk at 60-day follow-up, or in-hospital morbidity between liberal and restrictive transfusion groups [ 8 , [21] , [22] , [23] , [24] , [25] ]. Additionally, Murphy et al focused on a cohort of cardiac patients and showed no difference in morbidity and health care costs between liberal and restrictive transfusion guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could also not control for perioperative blood transfusions. It is likely, however, that blood administration and anaemia are both independently associated with postoperative mortality, [15] and we therefore believe that this weakness should not compromise the interpretation of our findings. Furthermore, it is also possible that the prevalence and severity of preoperative anaemia may have been underestimated in this study, owing to preoperative transfusions.…”
Section: Researchmentioning
confidence: 81%